2001
DOI: 10.1055/s-2001-11703
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Patient Strength, Aerobic Capacity and Body Composition Upon Outcomes After Coronary Artery Bypass Grafting

Abstract: Extrapleural pneumonectomy for diffuse malignant pleural mesothelioma was concluded to be a treatment option in stage Ib cases with epithelial histology. To evaluate precisely the efficacy of surgery for the disease, a randomized control trial must be organized multi-institutionally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 8 publications
0
37
0
4
Order By: Relevance
“…The quality of life of these patients was also improved and was maintained during the first 6 months after surgery. Cook et al [16] have also demonstrated that an exercise program and guidance on risk factors is beneficial to patients waiting for CABG, and was effective in reducing hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of life of these patients was also improved and was maintained during the first 6 months after surgery. Cook et al [16] have also demonstrated that an exercise program and guidance on risk factors is beneficial to patients waiting for CABG, and was effective in reducing hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have assessed the effect of regular physical activity in patients referred for coronary artery bypass grafting (CABG) [15][16][17]. The effect of leisuretime physical activity (LTPA) in the preoperative period on the incidence of major cardiac events (MCE), immediately after surgery in patients undergoing CABG is not well reported.…”
Section: Introductionmentioning
confidence: 99%
“…In Cook's study et al [12], patients with a history of prior physical activity reported better quality of life one year after CABG, even patients who had stopped physical activity for more than a year before the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Cook et al [12] sought to quantify the in-shape patients and determine whether it could improve the outcome in a Postoperative (179) group of patients referred for CABG. It was observed that patients with high body fat percentage and low aerobic capacity are at high risk for at least one postoperative complication, and a longer hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, questionnaire-based evaluations methods, such as those using the Veterans Specific Activity Questionnaire (VSAQ) and The Duke Activity Status Index (DASI), have been widely used in many countries and introduced into the textbook of the American College of Sports Medicine (8)(9)(10). In Japan, these questionnaire-based methods have been introduced into a number of exercise guidebooks for the assessment of cardiopulmonary function in circulatory disease and the evaluation of functional capacity recovery in the rehabilitation field, but whether these methods are applicable to Japanese elderly over the age of 75 is unclear (11,12).…”
Section: Introductionmentioning
confidence: 99%